Image Recording and Processing Chemical Synthesis - Sousa, David M. (2021)
This work was mainly funded by ERC‐CoG‐2014, ChapTherPV, 647596 and partially by H2020‐ICT‐2014‐1, RIA, TransFlexTeg, 645241, FEDER funds through the COMPETE 2020 Program and National Funds through FCT – Portuguese Foundation for Science and Technology with the reference SFRH/BD/135948/2018. Publisher Copyright: © 2020 The Authors. Published by Wiley-VCH GmbH.